2016
DOI: 10.1248/cpb.c15-00474
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Food/Drink to Reduce the Bitterness Intensity of Topiramate as Determined by Taste Sensor Analysis

Abstract: The purpose of this study was to determine which foods and/or drinks are capable of reducing the bitterness of topiramate when consumed together with the medicine. The inhibitory effects of foods/drinks (yoghurt and nine other foods/drinks) on the bitterness of topiramate (5 mg/mL) were evaluated with a taste sensor using a bitterness-responsive membrane (C00). The effect of topiramate on the taste characteristics of the foods/drinks themselves was also evaluated by taste sensor outputs. The viscosities of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…18,20,22,[25][26][27] The detecting sensor part of the equipment consists of a reference electrode and a taste sensor which acts as the working electrode and is composed of various types of lipid/polymer membrane. 36) Aqueous solutions (0.01, 0.05, 0.1, 0.5, 1.0, 2.0 mM) of basic drugs (DPH, DNP, AMD) were evaluated using taste sensor AN0, while phosphate-buffered saline (PBS) solutions (0.01, 0.05, 0.1, 0.5, 1.0, 2.0 mM) of acidic drugs (RBM, ETD and DCF) were evaluated using taste sensor AE1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,20,22,[25][26][27] The detecting sensor part of the equipment consists of a reference electrode and a taste sensor which acts as the working electrode and is composed of various types of lipid/polymer membrane. 36) Aqueous solutions (0.01, 0.05, 0.1, 0.5, 1.0, 2.0 mM) of basic drugs (DPH, DNP, AMD) were evaluated using taste sensor AN0, while phosphate-buffered saline (PBS) solutions (0.01, 0.05, 0.1, 0.5, 1.0, 2.0 mM) of acidic drugs (RBM, ETD and DCF) were evaluated using taste sensor AE1.…”
Section: Methodsmentioning
confidence: 99%
“…18,20,22,[25][26][27] We have previously shown that the basic bitter tastes of AMD and DPH could be evaluated using changes in membrane potential caused by adsorption (CPA) values obtained using taste sensor AN0 20,21) while the acidic bitterness of RBM could be evaluated using the relative values of taste sensor AE1, 18) both measurements providing good correlation with human sensory tasting. For this reason, in the present study we used CPA values of AN0 sensor output for the basic drugs AMD, DPH and DNP, while we used the relative values of the AE1 sensor output for the acidic drugs RBM, DCF and ETD.…”
Section: Taste-masking Effect Of Chlorogenic Acid (Cga) On Bitter Drumentioning
confidence: 99%
“…The taste sensor measurements were performed as follows, according to our previous articles. [28][29][30][31] The electrode set was attached to a mechanically controlled robot arm. The detecting sensor part of the equipment consists of a reference electrode and a working electrode composed The difference between the electric potential of the working electrode and the reference electrode was measured using a high-input impedance amplifier connected to a computer.…”
Section: Taste Sensor Measurement Of Pga Gel In the Absence Of Drug Amentioning
confidence: 99%
“…In the present study, we chose four drugs as model drugs, i.e., benazepril hy- The use of an "electronic tongue" or taste sensor for pharmaceutical purposes is an innovation which reduces dependence on human gustatory sensation testing. We have previously evaluated the bitterness of several registered basic or acidic medicines using the taste sensor [12] [23] [25]- [31].…”
Section: Introductionmentioning
confidence: 99%